Readibility, Understandability, and Quality of Online Education Materials for Vocal Fold Nodules - ENVER, NECATİ (MOSBY-ELSEVIER, 2020)
Objective. Vocal fold nodules are benign vocal fold lesions that can adversely affect quality of life. Differential diagnosis and treatment modalities of this disease are variable and patients often tend to use online materials to learn the insights. Access to knowledge via Internet is very easy; however, it is important to choose wisely because false and biased information might lead the patient to an inappropriate decision. In this study, we have evaluated the quality, readability, and understandability of online materials for vocal fold nodules. Methods. An Internet search was performed for Vocal fold nodule, vocal fold nodule treatment, and voice therapy for vocal fold nodule by using Google search engine. Readability of each website was evaluated by using v readable Understandability and actionability of pages were measured by using the Patient Education Materials Assessment Tool (PEMAT). In the end, DISCERN instrument was used to measure the quality of information presented. Results. After exclusion, total of 26 web pages were evaluated during the study. Four web pages graded as A level, 5 as B level, 11 as C level, and 5 as D level for language use. Average grade level for all of the web pages is 11.14 +/- 1.75. Overall understandability score was found 59.0+ 12.1 (26.7-77.1), and overall quality score was measured 34.95 + 6.58 (53.75-26.5). Conclusion. The quality, readability, and understandability of the written materials are very low and in order for patients to read and learn from the online sources, contents of the written materials should be revised.
Keywords: Vocal fold nodule; Online patient information; Readability; PEMAT; DISCERN; HEALTH INFORMATION; READABILITY; ACCURACY; WEBSITES; EAR; AGE